Faktor Yang Mempengaruhi Perilaku Konsumtif Dalam Berbelanja Online di E-Commerce (Studi Kasus Mahasiswa FEBI UINSU) - Hidayah, Muhammad Arif; Ridwan, Muhammad; Harahap, Muhammad Ikhsan (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to analyze the factors that affect consumptive behavior in online shopping in E-Commerce (Case Study of FEBI Uinsu students), while the independent variables in this study are motivation, lifestyle and advertising. This study uses primary data, with multiple linear regression data analysis method with SPSS tool.15.The respondents in this study amounted to 1001 people, using the sampling method with purposive sampling technique. Based on the results of the first hypothesis test, it is known that the significant value of motivation is 0.001 < 0.05 with a calculated t value of -3.348 < 1.985. The second hypothesis test showed the significance of lifestyle of 0.014 < 0.05 with a calculated t value of 9,254 > 1,985. And the third hypothesis test, it is known that the significant value of advertising is 0.000 < 0.05 with a calculated t value of 9,254 > 1,985. Based on the results of the fourth hypothesis test, it is known that a significant value of 0.000 < 0.05 with a calculated t value of 48.937 greater than F table 2.699 (F count > F table). The results of this study showed that motivation, lifestyle, and advertising simultaneously have a significant effect on well-being.